Kinerja Persimpangan Tidak Bersignyal Pada Ruas Jalan Imam Munandar-Bukit Barisan Kota Pekanbaru - Raja Andrian Maulana; Ari Sandhyavitri; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Recently the traffic growth in Pekanbaru is fast. The intersection of Imam Munandar Street and BukitBarisan Street has high traffic flow. Therefore, it is necessary to perform a study to analyze theintersection condition to cope with problems related to the performance of unsignalized intersection.The primary data was obtained by collecting real traffic data. The primary data was used in the analysisin accordance with MKJI 1997. The result of the analysis showed that the peak hour was on Tuesday at17:00 to 18:00 WIB, the peak traffic flow (Q) was calculated as 2126.1 smp/hour, the capacity ( C ) was1990.69 smp/h, the degree of saturation ( DS ) was 1.068, the delay of intersecton traffic (DT1) was18.86 sec/smp, the delay of intersection geometry (DG) was 3.94, the intersection delay (D) was 22.80,the queue probability ( QP ) was 45.98%-91.60%. These indicate that the intersection requires evaluationand improvement.Key words: capacity, degree of saturation, delay, queue opportunities, MKJI1997